Pharmacokinetics of 1, 25-dihydroxyvitamin D3 glycosides from Solanum glaucophyllum extract given in a rumen bolus on blood mineral profiles in dry pregnant dairy cows. (January 2022) - Meyer-Binzegger, M.; Ollagnier, C.; Eggerschwiler, L.; Bühler, K.; Schlegel, P.; Meylan, M.
Abstract: Providing tablets of 1, 25-dihydroxyvitamin D3 (1, 25(OH)2 D3 ), the biologically active metabolite of vitamin D3, in a rumen bolus may be used as prevention for periparturient hypocalcemia in dairy cows. This study investigated the pharmacokinetics of 1, 25(OH)2 D3 glycosides extracted from Solanum glaucophyllum (SGE) on blood serum 1, 25(OH)2 D3, Ca, P and Mg response in dry pregnant dairy cows. Boluses contained tablets of SGE which differed in their release properties (rapid release, slow release and combination) and galenics (200 μg uncoated, 300 μg and 500 μg uncoated or coated, 2 × 500 μg uncoated). Nineteen blood samples were collected from 29 cows between 96 h before and 336 h after bolus administration. Blood serum 1, 25(OH)2 D3, Ca and P increased between 12 h and 120 h, 12 h and 264 h and 24 h and 264 h, respectively. Highest values were reached at 30 h, 72 h and 120 h for 1, 25(OH)2 D3, Ca and P, respectively. Baseline values were then reached at 216 h for 1, 25(OH)2 D3 and 336 h for Ca and P. Concentration of Mg decreased between 24 h and 216 h, before reaching values comparable to baseline at 264 h. Highest Ca values were obtained with the combined rapid and slow release properties (500 μg) and there was no effect from coating on pharmacokinetics. In conclusion, the antepartum oral SGE bolus administration may be suitable for the prevention of periparturient hypocalcemia. Graphical abstract: Unlabelled Image Highlights: Solanum glaucophyllum extract delivered reliable amounts of 1, 25(OH)2 D3 glycosides. Application of one oral bolus increased serum calcium over several days. No adverse effects were observed even after simultaneous application of two boluses. Antepartum oral bolus administration may be suitable for periparturient hypocalcemia prevention.